Prognostyczne aspekty cech ubezpieczyciela na przykładzie ryzyka wyceny zabezpieczenia długoterminowego - Balcerowicz-Szkutnik, Maria; Szkutnik, Włodzimierz; Wolny, Alicja (Aspects Forecast of Firm Traits on Long-Term Care Insurance Pricing, 2006)
The article shows the modeling of the long-term individual insurance valuation in the scope of securitization of elderly people. The hedonic model presented here has the form of description of influence of insurance companies' features in life insurance department on insurance valuation, it means premium taking into consideration operational variables, such as organizational form Fo, ln (assets), ln (act)RBC coefficient, duration in the market tr. These variables characterize influence of moral hazard and adverse choice on price and they should be taken into consideration on they enable to achieve results of researches consistent with policy planned variable controlling moral hazard ex post.Long-term insurance market becomes stable but there are constant dangesso it will reveal many new possibilities for additional researches. Prognosis values of hedonic model indicate the possibility of future long-term insurance valuation moulding. The examination of publicly accessible and common policy is based on the advantages of informing consuments about the scope of available long-term insurance products aiming at encouraging to increase solutions for potential social problems related to private market financing risk. Since the researchers strive to examine these and other issues related to long-term insurance, the lack of data may disturb their initiative, taking into consideration the tendency to increase the market power by a little group of insurers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 145-159